Accelerometers attached to chick-rearing murres in 2010, Part 1 - Elliott, Kyle H.; Hare, James F.; Le Vaillant, Maryline; Gaston, Anthony J.; Ropert-Coudert, Yan; Anderson, W. Gary (Dryad Digital Repository, 2014)
Accelerometer files produced by Little Leonardo accelerometers. Each subfolder has the last five digits of the band number of the individual murre to whom the accelerometer was attached, and serves as the unique identifier to cross-reference with other information (sex, age, etc.). Within each folder, there are five files: the raw data (obj) file and a text file for the temperature log (in degrees C, every 1 s), depth (in m, every 1 s) and acceleration in the X and Y directions, in 32 Hz increments.